The Application of Binary Numbers in Digitalization - Martono, Stefany Margareta; Suryani, Luluk; Van Harling, Vina N (SOSCIED, 2025)
Education today is driven to adapt to the demands of the modern era, particularlythrough the integration of technology into the learning process. The implementation of digital-based binary number learning provides students with a foundational understanding for developing programs, games, and even simple electronic circuits. This approach encourages students to innovate and be creative in designing technology products based on binary numbers—0 and 1. This study was conducted at SMP Cinta Kasih in Sorong City. The researcher carried out classroom observations and collaborated with the teacher to design and implement this learning model for Grade 8 students. A quantitative research method was employed. Digital-based learning was implemented using the Tinkercad application. Data were collected from students’ performance scores, which were compiled into an assessment rubric and conducted through group activities. The findings indicate that the students’ final mean score was 79.769, which falls into the “competent” category. This suggests that students at SMP Cinta Kasih possess adequate competence in applying digital-based binary number concepts.